OPTIMIZATION OF PRESERVATIVE FOR PROTECTION OF CONCRETE PAVEMENT OF HIGHWAYS - M. K. Pshembaev; Ya. N. Kovalev (Наука и техника)
Disadvantages of road concrete pavement quite well known professionals-standards. They were mainly low elasticity modulus asphaltic concrete, as well as a fairly rapid aging of asphalt concrete core component-bitumen. And, as a consequence, is relatively low durability of the coating, the need for frequent repair. To some extent, cement concrete cover signifi cantly outperform this index of asphalt, convinces experience roads of Germany, the United States and other countries. The correct structure of concrete, overall compliance technology laying concrete, comprehensive quality control production  work, sufficient technical personnel qualifications provide long defect-free work road re-coated. However, violations by manufacture of works or in the process of exploitation, particularly in the harsh conditions of freezing and thawing, saturation-drying, especially under the influence of salts-defrosting, cause defects, reduce its durability. There are two directions of increase of durability of the coating. Firstly, it is the primary protection is the creation of concrete with minimal possible on data components mixture water cement ratio that provides reception of concrete with minimum porosity and consequently with maximum durability. Secondly, the secondary protection, providing increased resistance already ready-mixed concrete cover external aggressive actions. In this case against the background of other ways quite promising looks impregnation of the surface concrete integrated structure. Composition must contain multiple components, primarily water repellents, preventing penetration of fluid into the body of the concrete, and finely dispersed silica sol in particular silica, providing reduction of the porosity of the surface layers of concrete by interacting with the free calcium hydroxide. The problem of optimization of impregnation structure and is dedicated to this work.